Safety and immunogenicity of a plant-derived recombinant protective antigen (rPA)-based vaccine against Bacillus anthracis: A Phase 1 dose-escalation study in healthy adults. Issue 12 (15th March 2022) - Paolino, Kristopher M.; Regules, Jason A.; Moon, James E.; Ruck, Richard C.; Bennett, Jason W.; Remich, Shon A.; Mills, Kristin T.; Lin, Leyi; Washington, Cadeidre N.; Fornillos, Ghariwayne A.; Lindsey, Changhong Y.; O'Brien, Kristan A.; et al.
Highlights: Assessment of plant-produced recombinant PA83 antigen in humans. All dose ranges tested were safe and immunogenic. Immunogenicity is dose dependent and peaked one month after the final vaccine administration. Abstract: Background: The potential use of Bacillus anthracis as a bioterrorism weapon requires a safe and effective vaccine that can be immediately distributed for mass vaccination. Protective antigen (PA), a principal component of virulence factors edema toxin and lethal toxin of B. anthracis, has been the topic of extensive research. Previously, full-length PA (PA83) was manufactured using a transient plant-based expression system. Immunization with this PA83 antigen formulated with Alhydrogel® adjuvant elicited strong neutralizing immune responses in mice and rabbits and protected 100% of rabbits from a lethal aerosolized B. anthracis challenge. This Phase 1 study evaluates this vaccine's safety and immunogenicity in healthy human volunteers. Methods: This first-in-human, single-blind, Phase 1 study was performed at a single center to investigate the safety, reactogenicity, and immunogenicity of the plant-derived PA83-FhCMB vaccine at four escalating dose levels (12.5, 25, 50 or 100 µg) with Alhydrogel® in healthy adults 18–49 years of age (inclusive). Recipients received three doses of vaccine intramuscularly at 28-day intervals. Safety was evaluated on days 3, 7, and 14 following vaccination. Immunogenicity was assessed using an enzyme-linked immunosorbent assay (ELISA) and a toxin neutralizing antibody (TNA) assay on days 0, 14, 28, 56, 84, and 180. Results: All four-dose ranges were safe and immunogenic, with no related serious adverse events observed. Peak ELISA Geometric Mean Concentration (GMC) and TNA ED50 Geometric Mean Titer (GMT) were noted at Day 84, 1 month after the final dose, with the most robust response detected in the highest dose group. Antibody responses decreased by Day 180 across all dose groups. Long-term immunogenicity data beyond six months was not collected. Conclusions: This is the first study demonstrating a plant-derived subunit anthrax vaccine's safety and immunogenicity in healthy adults. The results support further clinical investigation of the PA83-FhCMB vaccine. ClinicalTrials.gov identifier. NCT02239172.